Biomarkers and prognostic factors for malignant pleural mesothelioma. (November 2015) - Vigneri, Paolo; Martorana, Federica; Manzella, Livia; Stella, Stefania
The increasing incidence and the dismal prognosis of malignant pleural mesothelioma calls for the identification of biomarkers that will allow a timely diagnosis; display prognostic value; and, predict the response to pharmacological agents employed for the treatment of the disease. Biomarkers associated with early diagnosis currently include mesothelin in combination with miRNA miR-103a-3p. As for prognostic biomarkers, the Cancer and Leukemia Group B (CALGB) and the European Organization for Research and Treatment of Cancer (EORTC) scores take into account different hematological and clinical parameters that distinguish patients with good prognosis from those with inferior outcomes. Fluorodeoxyglucose-PET, microarray expression data, neutrophil-to-lymphocyte ratios, c-MET expression, Ki-67 ratios and fibulin-3 levels have also been associated with disease outcome. Finally, thymidylate synthase protein cutoffs may predict mesothelioma response to the association of pemetrexed with a platinum derivative.